Indeks Nilai Penting Dan Berat Jenis Kayu Pada Beberapa Lahan Agroforestry Di Kawasan Penyangga Taman Nasional Kelimutu - Anasaga, Agustinus J.P (AGRICA, 2024)
This study investigates the importance of the value index and wood-specific gravity in the buffer area of Kelimutu National Park. The method used is Nested Sampling Design (NSD). The research results show that there are 15 species of agroforestry land in Kelimutu National Park that are based on cloves (AF-CV), cocoa (AF-CC), candlenuts (AF-CL), and coffee (AF-CF). In AF-CV with a breast diameter (DBH) less than 30 cm, the dominant species is jackfruit (Artocarpus heterophyllus) (IVI 101%). AF-CL  with DBH less than 30 cm is dadap (Erythrina varie); DBH more than 30 cm is candlenut (Aleurites moluccanus), IVI 104%). coffea (IVI 155%), and mahagoni (Swietenia mahagoni) (IVI 100%). Based on the trunk diameter (DBH) and SG of the wood, two types of wood have light SG: AF-CC (82%), AF- CF (88%), and AF-CL (7%). Secondly, if DBH is more than 30 cm, light SG in AF-CL (96%) and moderate SG in AF-CV (98%).  The wood SG value in AF-KM (0.58 g m3) is the same as the other three Agroforestries, with an average of 0.49 g m3 ha-1.